METODE DAN MEDIA PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI SEKOLAH DASAR ANTARA PERSEPSI SISWA DAN GURU - Ulfah, Risti Aulia; Feriandi, Yoga Ardian (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
This research aims to examine what learning methods and media are considered ideal from the perspective of students and teachers. Learning methods and media play an important role in the learning process. Learning methods are the methods used by teachers to convey learning so that it is easy for students to understand. Meanwhile, learning media is a tool used by teachers to convey learning material so that learning can take place effectively and efficiently. The use of learning media in learning is the teacher's effort to make it easier for students to accept and achieve the learning goals that have been set. The development of technology and globalization has had an impact on learning media which must also be able to adapt to current trends and developments. This research was carried out at SD Negeri Kebon 1, Paron District, Ngawi Regency. This research uses a quantitative descriptive method with purposive sample selection. The research population and sample are class teachers and students in grades V and VI. The research results show that there are differences in views between students and teachers regarding learning methods and media, especially when viewed from the different characteristics of each generation (students and teachers) and produce different views.